(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
Certainly there is a negative impact on development due to corruption in its corruption forms It is administrative and financial as well as direct impact on all sectors Including the health sector, which has seen in Iraq a marked setback in performance and services , The research aims at the possibility of demonstrating the negative effects of financial and administrative corruption on health institutions and Inability to meet health needs The extent to which Regulatory institutions and institutions manage to reduce financial and administrative corruption and ways of dealing with it The phenomenon of financial and administrative corruption is the most serious phenomenon because of its impact on economic growth, which in turn impedes the achievement of goals. through This research will be highlighting the serious consequences And the negative effects generated by administrative and financial corruption in the health institution. In view of this The research The research included four axes (research methodology, the concept of financial and administrative corruption, the concept of health control, conclusions and recommendations).